Meningkatkan Kemampuan Menulis Puisi Melalui Media Audio Visual pada Siswa Kelas VIII SMP Negeri 4 Klari (International Forum of Researchers and Lecturers, 2024)
This study aims to examine the achievement and improvement of poetry writing skills of class VIII students of SMP Negeri 4 Klari who use audio-visual media. This is in line with the problem of the low poetry writing skills of junior high school students. In reality, the ability to write poetry is one of the important aspects of language to be learned and mastered well. The method used in this study was an experiment with a pretest-posttest control group design. The population in this study were all class VIII students of SMP Negeri 4 Klari, Karawang Regency. Sampling using cluster sampling technique, two classes were selected as research samples, namely class VIII-G (control class) which used direct learning totaling 37 students, while class VIII-H (experimental class) which used audio-visual media totaling 39 students. The research instrument used a poetry writing ability test. Both classes were given a pretest, treatment, and posttest with the same questions. Quantitative data analysis of the study utilized statistical calculations using SPSS 21 software. It can be seen from the results of calculations with SPSS 21 software that the Asymp. Sig. value was obtained. (2-tailed) of 0.000 is less than the significance level (α) of 0.05. Thus, the results of this study indicate that the achievement and improvement of students' poetry writing skills who receive learning with audio-visual media are better than students who receive direct learning.